Reflexões sobre signo ideológico (Volóchinov) e discurso oculto (Scott): discurso linguístico como via de resistência - Ana Paula André (Revista Odisséia)
This article has resistance and the ideological sign as its object of study. Its objective is to reflect on the thoughts of Valentin Voloshinov and James Scott, who problematize issues related to ideology, demonstrating the correlations between the ideological sign, from Voloshinov’s perspective, and everyday resistance, elaborated by Scott. It is justified by the need to understand hidden discourses as resistance and space of struggle. Regarding the methodology, this article is based on a theoretical research with a critical review of literature. It presents as a result the discursive ideological sign as a reflection of reality and a material fragment of it, through which resistance occurs daily, against the system of domination, in different places of speech, taking into account the relations of power and subordination. Such resistance often occurs in a camouflaged manner, distant from legitimate public discourses, but still as an expression of struggle. Through the research, it was concluded that the authors’ theoretical elements dialogue with each other, understanding the subject as a result of social interactions and submerged in power relations.